The Exports of the Southern Region of Brazil: An Analysis of the Agricultural Sector - Claudy da Silveira, Daniel (2019)
This article aims to analyze the trade flows of the main products of the agricultural sector (soybean, tobacco and meat) exported by the Southern Region of Brazil, its main target market (Argentina, China, United States and European Union), through a gravitational model, estimation of panel data, with the approach of ordinary least squares (OLS - Pooled), from 2000 to 2012. The estimation of the gravity model results showed that the estimates follow the seminal works of economic literature. The same is shown that, in the analyzed period, the flow of the agricultural sector of the Southern Region suffer negative influence of the distance between countries and, on the other hand, positively in relation to the mass population and the real exchange rate on trade flows between countries considered.